Sociodemographic Associations of Dementia Literacy in Older Australians - Joyce Siette; Laura Dodds (Journal of Ageing and Longevity, 2022)
Recent levels of dementia literacy in older Australian adults remains relatively unexplored. Our purpose was to identify whether dementia literacy has changed in older Australians, sociodemographic characteristics associated with better literacy, and barriers to dementia risk reduction. A 32-item adapted British Social Attitudes Survey was administered to 834 community-dwelling older adults (mean age 73.3, SD = 6.0, range 65–94) on dementia awareness and knowledge of dementia risk and protective factors. Descriptive analyses, logistic, and multiple linear regressions were used to examine sociodemographic factors on dementia awareness and literacy. Most respondents (61%) were aware of the relationship between different lifestyle factors and dementia risk, with the majority reporting cognitive (85.0%) and physical inactivity (83.4%) as key risk factors. Few were able to identify less well-known factors (e.g., chronic kidney disease; 15.8%). Individuals with higher educational attainment were more likely to agree that dementia is modifiable (OR 1.228, 95% CI 1.02–1.47). Younger age (β = −0.089, 95% CI −0.736–−0.065, p = 0.019) was significantly associated with a higher number of correctly-identified dementia risk factors. Lack of knowledge was the key barrier to hindering dementia risk reduction. A tailored, evidence-informed, population-based lifespan approach targeting dementia literacy may help alleviate commonly reported barriers and support dementia risk reduction.